Ionic liquids (iLs)as the solvent for synthesis of nanoparticles - Wan Muhamad Faiz Wan Abd Aziz, Wan Muhamad Faiz (2009)
In this project there are some of concepts need to be understand before proceeding to the next stage. Under this topic, there are nanoparticles, ionic liquids and sample characterization test topics. Theses are the main point in this project.